Error Analysis Of Students Translations on Descriptive Text Based on Villar et al. (2006) - Wistawati; Mochamad Rizqi Adhi Pratama (Universitas Ngudi Waluyo, 2025)
Translation is required by foreign language learners as it is one of the crucial tasks in the process of information exchange. This study aims to explore the translations made by students based on Vilar et al.'s theory which emphasises statistical machine translation errors and difficulties experienced by students, where the errors occur, as well as the percentage of each error in the translations made by students. This study took the subject of 12th grade students of SMA Negeri 2 Ungaran in the 2024-2025 academic year. In this study, the expected result is that students are able to translate Indonesian into English well in terms of vocabulary and grammar, with minimal errors. This study used descriptive qualitative method to analyse the data. The subjects of this study were 36 students. The tool used in this study was a test. After undergoing the test conducted, the findings showed that there were 13 students who committed missing word errors, 7 students who committed additional word errors, 8 students who committed wrong word errors, 8 students who committed punctuation errors, and 0 students who committed unknown word errors. Based on these results, it can be concluded that students still have difficulties in translation practice.